Analysis of Income and Welfare of Corn Farmers Viewed From an Islamic Perspective in Pungkit Village, Moyo Utara District: Analisis Pendapatan dan Kesejahteraan Petani Jagung dilihat dari Perspektif Islam di Desa Pungkit Kecamatan Moyo Utara - Mulianti, Dara Elis; Muaidy Yasin; Moh. Huzaini (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2023)
This study aims to analyze the income and welfare of corn farmers in the context of an Islamic perspective in North Moyo District. This study used a qualitative approach by collecting data through interviews and documentation. The data obtained is related to the income of corn farmers in the sub-district which is influenced by capital, production costs, land area, selling price, and labor. Based on the research results, it was concluded that the income from corn farming in Pungkit Village, North Moyo District, reached a total cost of IDR 1,178,561,000. This income is influenced by factors such as production costs, land area, selling price, labor, and capital. The income level of corn farmers in one corn season can be seen from these factors. In the view of Islamic economics, the income of corn farmers in Pungkit Village, North Moyo District, cannot be said to be good because it involves capital production factors obtained through non-halal methods, such as loans from banks or moneylenders. Taking or borrowing money from banks or moneylenders is forbidden according to Islamic teachings as explained in the Qur'an and hadith. In terms of welfare, the majority or all corn farmers have achieved a good life (hayaatan tayyibah) and have sufficient halal sustenance. They are also able to meet the spiritual needs of their families and are satisfied with what they receive despite living in simplicity, because they are able to meet the dharuriyyat (basic needs) and hajiyat (additional needs) needs.